Typology and effects of crimes against public administration in Colombia (2020)
The misconduct exercised by public officials or servants today are classified as crimes against the public administration, evidencing the use of excesses exercised in the development of the public function; which in turn deteriorate the patrimony of the state. Crimes against the public administration are those punishable behaviors that do not account for a good management of state resources. The Colombian Penal Code, Law 599 of 2000, establishes crimes against the public administration, classifying some of them as embezzlement, concussion, prevaricate, illicit enrichment, bribery, the undue conclusion of contracts, influence peddling, generating distrust and lack of ethics and morals in the institutions. Nowadays it is fundamental that the public servant be a person of integrity endowed with values which are the fundamental pillar of the development of their functions; avoiding falling into unethical conducts that affect or deteriorate the patrimony of the state, and even end up disabled or assuming crimes that were previously typified. The official may be involved in a type of civil, criminal, Fiscal, Administrative and Disciplinary responsibility if he does not perform his functions under the principles of morality and transparency.